Influence of water deficit on the production and quality of Piptadenia moniliformis Benth. seedlings - da Silva Costa, Jenickson Rayron; de Holanda, Alan Cauê; Pinheiro, Ewerton Souto; dos Santos Silveira, Gleydson Vinicius; Alves, Allyson Rocha; da Silva, Magali Ribeiro [UNESP] (Centro Universitario de Maringa, 2023)
Assessing seedling quality and reducing the initial amount of water used for irrigation in the development phase is an important strategy to predict post-planting field survival to make seedling production less costly. Therefore, the objective was to evaluate the quality of Piptadenia moniliformis Benth seedlings, under different irrigation intervals. The experiment was completely randomized with thirty-five seedlings (5 treatments x 7 replications). Biometric measurements were performed for up to 90 days. Seedlings irrigated for up to 6 days showed superior results in parameters that indicate the quality of seedlings, such as Height/Diameter Ratio (H/D) and Dickson Quality Index (DQI). In the early stage of development, an irrigation interval of up to 6 days is adequate to produce quality P. moniliformis seedlings.
Influência do déficit hídrico na produção e qualidade de mudas de Piptadenia moniliformis Benth
Keywords: Caatinga biome; Catanduva; Principal component analysis; Watering intervals